1
$\begingroup$

Consider a recent arXiv preprint 1805.11445. The author of 1805.11445 has done an overview of classical problem of simplifying of power sum

$$\sum_{1\leq k\leq n}k^m, \ (n,m)\geq 0, \ m=\mathrm{const}$$

and proposed "A Fast Algorithm to Calculate Power Sum of Natural Numbers". The follow identites are found in 1805.11445 for $\Sigma_{1\leq k\leq n} k^4$ and $\Sigma_{1\leq k\leq n} k^{12}$,

$$\sum_{1\leq k\leq n} k^4=\binom{n+4}{n-1}+11\binom{n+3}{n-2}+11\binom{n+2}{n-3}+\binom{n+1}{n-4}$$

And, respectively

\begin{eqnarray*} % \nonumber to remove numbering (before each equation) \sum_{1\leq k\leq n} k^{12} &=& \binom{n+12}{n-1}+4083\binom{n+11}{n-2}+478271\binom{n+10}{n-3} \\ &+&10187685\binom{n+9}{n-4}+66318474\binom{n+8}{n-5}+162512286\binom{n+7}{n-6}\\ &+&162512286\binom{n+6}{n-7}+66318474\binom{n+5}{n-8}+10187685\binom{n+4}{n-9}\\ &+&478271\binom{n+3}{n-10}+4083\binom{n+2}{n-11}+\binom{n+1}{n-12} \end{eqnarray*}

Now we have to mention that the coefficients in corresponding sums $\Sigma_{1\leq k\leq n} k^4$ and $\Sigma_{1\leq k\leq n} k^{12}$ are terms of forth and twelfth rows of Eulerian Triangle. Therefore, we have right to generalize above identities as follows

$$(\star)\quad\sum_{1\leq k\leq n} k^{m}=\sum_{k\geq0}E_{m,k}\binom{n+m-k}{n-1-k}$$

that is analog of Faulhaber's formula for every positive integers $(n,m)$.

Question: Is there any reference to equation $(\star)$ ?

$\endgroup$
1
$\begingroup$

Result in this question is direct consequence of Worpitzky Identity and Symmetry of Binomial coeficients. Recall the power sum, see Wikipedia

$$(\ast)\quad\sum_{k=1}^{n} k^{m}=\sum_{k=0}^{m-1}E_{m,k}\binom{n+1+k}{m+1}$$

Now, let compare the binomial coefficients in $(\star)$ and $(\ast)$, we start to check from the values of corresponding binomial coefficients for $k=0$ and $k=m-1$ respectively, we have

$$\binom{n+m-(m-1)}{n-1-(m-1)}\equiv \binom{n+1}{m+1}\rightarrow \binom{n+1}{n-m}=\binom{n+1}{m+1}$$ Therefore, denote $j=n+1$ and $r=m+1$, symmetry of binomial coefficients holds $$\binom{j}{r}=\binom{j}{r-j}$$ Now if we substitute the step $a$ instead $1$, the identity holds again

$$\binom{n+a}{n-m}=\binom{n+a}{m+a}$$ Therefore, Worpitzky Identity implies $$\sum_{k=1}^{n} k^{m}=\sum_{k=0}^{m-1}E_{m,k}\binom{n+1+k}{m+1}=\sum_{k=0}^{m-1}E_{m,k}\binom{n+m-k}{n-1-k}$$

$\endgroup$

Your Answer

By clicking "Post Your Answer", you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.